MicroRNA Regulation in Osteogenic and Adipogenic Differentiation of Bone Mesenchymal Stem Cells and its Application in Bone Regeneration - Li, Binbin (Current Stem Cell Research & Therapy, 2018)
Background: Bone mesenchymal stem cells (BMSCs) are multipotent stromal cells providing a useful cell source for treating bone diseases and metabolic disorders. BMSCs fate determination and lineage progression are controlled by multiple cytokines, transcriptional factors, signaling pathways, and microRNAs (miRNAs). MiRNAs are small non-coding RNAs that inhibit the posttranscriptional gene expression or degrade their targets. They are closely involved in controlling the key steps of osteogenesis and adipogenesis of BMSCs. Objective: We aim to summarize the roles of miRNAs and their pathways in regulating osteogenic and adipogenic differentiation of BMSCs, and sketch its preliminary applications in bone regeneration. Method: We reviewed the published literature about the microRNA regulation in osteogenic and adipogenic differentiation of BMSCs. Results: Most of miRNAs are expressed in BMSCs, perform as negative regulators of osteogenesis and have bidirectional effects on adipogenesis. Runx2 and PPARγ are two key transcriptional factors in osteogenesis and adipogenesis, respectively. Conclusion: Anti-miRNAs or miRNA mimics is potential therapeutic strategy to repress pathological miRNAs for cellular therapies to bone diseases. The preliminary applications of miRNAs in BMSCs strongly suggested their bright future in bone regeneration.
Keywords: bone mesenchymal stem cell